PROFESSIONAL ENGINEERING KNOWLEDGE AS A COMPONENT OF PROFESSIONAL COMMUNICATIVE COMPETENCE IN ENGLISH - Karshieva, B.F. (Educational Research in Universal Sciences, 2022)
The principles of integration based on interdisciplinary connections and the fundamental principles of educational content remain effective and gain new adherents. The concept of integration is considered by researchers as an educational principle that provides interdisciplinary complexity, generalization, density of knowledge, methods and tools of knowledge. Integration allows for a fragmented study of the conflict between the multifaceted and systematic-integral nature of education with a global character of philosophical concepts and goals through the subject type of education.